Hubungan Motivasi Dengan Kepatuhan Diet Pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Ketapang 1 Sampit - Mely Maulydia Anggraini; Maulana Arif Murtadho (Jurnal Keperawatan Muhammadiyah, 2026)
Dietary adherence is a crucial element in managing Diabetes Mellitus, yet many patients struggle to follow the dietary guidelines prescribed by healthcare providers. Motivation plays a central role in this adherence; patients with high motivation demonstrate stronger commitment and consistency in following the recommended diet, while those with low motivation face a much greater risk of failing to comply. This study aimed to investigate the link betwen motivations and dietary adherence in patients with Type 2 Diabetes Mellitus at Ketapang 1 Sampit Health Center, emphasizing the critical role of motivation in ensuring compliance and effective disease management. This research employed an observational quantitative design with a cross-sectional approach, involving 60 respondents selected through accidental sampling. The study was carried out from September 26 to October 18, 2025. Data were collected using the Treatment Self-Regulation Questionnaire (TSRQ) and a Dietary Adherence questionnaire. The results were analyzed use the Spearman rho statistic test, which produced a p-value of <0.001 (p < 0.005). The findings indicate that most participants demonstrated a high level of motivation, with 46 respondents (76.7%) falling into this category. Among them, 28 respondents (46.7%) showed good adherence to dietary guidelines, while 18 respondents (30.0%) exhibited moderate adherence. Statistical testing produced a p-value of <0.001 (p < 0.005), confirming a significant association between self-motivation and dietary compliance among individuals with Type 2 Diabetes Mellitus at the Ketapang 1 Sampit Health Center. Furthermore, the correlation coefficient (r = 0.791) reflects a strong and positive relationship between motivation and dietary adherence in this patient group. These results highlight the importance of strengthening patient education programs, particularly those aimed at enhancing motivation, so that dietary management can be maintained consistently over time. Keywords : Dietary adherence, motivation, type 2 diabetes mellitus diet management, people with type 2 diabetes mellitus, health behaviors.